2014
DOI: 10.1186/1741-7015-12-68
|View full text |Cite
|
Sign up to set email alerts
|

Risks and benefits of transfusion for children with severe anemia in Africa

Abstract: Severe anemia contributes significantly to child mortality in sub-Saharan Africa. Blood transfusion is used in emergencies but carries risks. In BMC Medicine, Olupot-Olupot and colleagues report the findings of a phase II trial in children with severe anemia in Eastern Uganda. They provide important early safety and efficacy data supporting large volume whole blood transfusion (30 ml/kg) compared with the World Health Organization recommendation of 20 ml/kg. Large volume transfusions result in more rapid and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Second, for the two studies [ 15 , 16 ] that reported separate data for transfused and non-transfused children, we examined the individual case fatality rates for these groups in order to justify the exclusion of transfused subjects. These analyses were performed because blood transfusion is a potentially lifesaving intervention [ 17 ] that improves Hb and, thus, could modify the risk relation in which we were interested. Third, for the one study [ 18 ] that reported data for groups of children who were aparasitemic, parasitemic and parasitemic with malaria, we evaluated the risk relation separately for each of these groups.…”
Section: Methodsmentioning
confidence: 99%
“…Second, for the two studies [ 15 , 16 ] that reported separate data for transfused and non-transfused children, we examined the individual case fatality rates for these groups in order to justify the exclusion of transfused subjects. These analyses were performed because blood transfusion is a potentially lifesaving intervention [ 17 ] that improves Hb and, thus, could modify the risk relation in which we were interested. Third, for the one study [ 18 ] that reported data for groups of children who were aparasitemic, parasitemic and parasitemic with malaria, we evaluated the risk relation separately for each of these groups.…”
Section: Methodsmentioning
confidence: 99%
“…It has a connection with immunological factors, genetic factors, and neurological issues in general. Vitiligo has been linked to autoimmune and endocrine problems in a few cases [8,9]. The disease is a refractory disease with a protracted and difficult treatment cycle, whereas patients with a brief disease phase have an optimal therapeutic outcome.…”
Section: Introductionmentioning
confidence: 99%
“…the period between the donor's infection and the appearance of infection markers in his blood. This is also due to fact that detecting the disease during this time is im-possible [55,60]. Blood-borne pathogens also include Cytomegalovirus (CMV) or protozoa of the genus Babesia [61][62][63].…”
Section: Complications After Transfusion Of Blood and Blood Componentsmentioning
confidence: 99%
“…Non-infectious serious hazards of transfusion (NISHOTs) are usually complications fol-lowing transfusion of blood products in neonates. In neonatal intensive care units, necrotising enterocolitis (NEC), bronchopulmonary dysplasia (BPD), retinopathy of prematurity (ROP), intraventricular haemorrhage (IVH) and abnormal development of the nervous system have been observed most frequently [60,29]. Necrotising enterocolitis (NEC) particularly affects extremely low birth weight (ELBW) neonates and 5% of neonates born prematurely.…”
Section: Complications After Transfusion Of Blood and Blood Componentsmentioning
confidence: 99%